QUALITY OF INPATIENT MEDICAL SERVICES AT THE NATIONAL GERIATRIC HOSPITAL IN 2026 AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of inpatient examination and treatment service quality at the National Geriatric Hospital in 2026 and analyze several related factors.Methods: A cross-sectional descriptive study design was conducted to assess patients’ perceptions based on the standardized SERVPERF scale, which includes 5 dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were analyzed using Cronbach’s Alpha reliability test, exploratory factor analysis, and multivariate regression models.Results: The hospital’s inpatient service quality was evaluated at a very high level, with an overall mean score of 4.51 ± 0.41. The assurance dimension achieved the highest score (4.68 points), followed by empathy (4.58 points), reliability (4.57 points), responsiveness (4.49 points), and the lowest was tangibles (4.25 points). The study also indicated that individual patient characteristics, including education level, occupation, residence, and health insurance status, had significant associations with perceptions of service quality.Conclusions: The National Geriatric Hospital has successfully demonstrated its strengths in medical professional capacity and humane care attitude. To fully optimize the experience of elderly patients, the hospital needs to prioritize investment in improving physical infrastructure (tangible factors) and streamlining inpatient service processes.
Keywords: Service quality, SERVPERF, inpatient treatment, National Geriatric Hospital.